Functional characterization of the schizophrenia associated gene AS3MT identifies a role in neuronal development. Issue 5 (19th June 2022) - Washer, Sam J.; Flynn, Robert; Oguro‐Ando, Asami; Hannon, Eilis; Burrage, Joe; Jeffries, Aaron; Mill, Jonathan; Dempster, Emma L.
Abstract: Genome‐wide association studies (GWAS) have identified multiple genomic regions associated with schizophrenia, although many variants reside in noncoding regions characterized by high linkage disequilibrium (LD) making the elucidation of molecular mechanisms challenging. A genomic region on chromosome 10q24 has been consistently associated with schizophrenia with risk attributed to the AS3MT gene. Although AS3MT is hypothesized to play a role in neuronal development and differentiation, work to fully understand the function of this gene has been limited. In this study we explored the function of AS3MT using a neuronal cell line (SH‐SY5Y). We confirm previous findings of isoform specific expression of AS3MT during SH‐SY5Y differentiation toward neuronal fates. Using CRISPR‐Cas9 gene editing we generated AS3MT knockout SH‐SY5Y cell lines and used RNA‐seq to identify significant changes in gene expression in pathways associated with neuronal development, inflammation, extracellular matrix formation, and RNA processing, including dysregulation of other genes strongly implicated in schizophrenia. We did not observe any morphological changes in cell size and neurite length following neuronal differentiation and MAP2 immunocytochemistry. These results provide novel insights into the potential role of AS3MT in brain development and identify pathways through which genetic variation in this region may confer risk for schizophrenia.